The legacies of the repatriation of human remains from the Royal College of Surgeons of England - Morton, S (2017)
The repatriation of the human remains of Indigenous peoples collected within a colonial context has been the subject of debate within UK museums over the last 30 years, with many museums now having returned human remains to their countries of origin. Although the repatriation of human remains is often characterised as the 'journey home', there has been a lack of consideration of the physical presence and mobility of the remains and the meanings created as they move through different spaces. This study uses the repatriations from The Royal College of Surgeons of England (RCS) to Australia, New Zealand and Hawaii as case studies to consider three key areas: (i) the impact of repatriation on museum landscapes; (ii) the journey of the repatriated remains and how this mobility intersects with wider discussions about restitution, sovereignty, identity, relatedness, memory and memorialisation; and (iii) the repatriation archives, how they are thought about by the institutions that hold them and their future potential and meaning within a post-colonial context. Taking a more-than-representational approach and engaging with the materiality, mobility and agency of the repatriated remains and the documentation that relates to them, this study bridges the gap between research considering the approach of museums to repatriation, and ethnographic studies on the meanings of the return of ancestral remains to individual communities. Combining work on museum geographies, deathscapes and absence opens up new ways of theorising and discussing repatriation through understanding the process in terms of the tension between absence and presence, and human remains as being in or out of place. Through engaging with the materiality and agency of the remains and viewing repatriation through a spatial lens, this thesis deals with aspects of the process that have received little attention in previous studies, foregrounding the challenging nature of repatriation for communities, the issues around unprovenanced remains, and discussions about the control, management and meaning of information and data, identifying that a significant legacy of repatriation for RCS is the documentation the museum continues to hold. What the journey of the ancestral remains repatriated by RCS illustrates is the emotive materiality of the remains, and agency that they and the distributed repatriation archive have as actors within social networks. It is therefore proposed that the concept of repatriation as having problematised human remains collections within UK museums is replaced with a nuanced and contextually sensitive understanding that recognises the role of the human remains in social interactions that impact on the emotional geographies of museum practice, and that rather than framing repatriation as post-colonial act that is either political or therapeutic, the return of ancestral remains be understood as part of a process of decolonisation in which there is space for discussion, disagreement and debate amongst all stakeholders.